Surveillance, anticipation and firefighting: Perspectives of patient safety from a New Zealand case study. (11th April 2019) - Wailling, Jo; Robinson, Brian; Coombs, Maureen
Abstract: Aim: This study explored how doctors, nurses and managers working in a New Zealand tertiary hospital understand patient safety. Background: Despite health care systems implementing proven safety strategies from high reliability organisations, such as aviation and nuclear power, these have not been uniformly adopted by health care professionals with concerns raised about clinician engagement. Design: Instrumental, embedded case study design using qualitative methods. Methods: The study used purposeful sampling, and data was collected using focus groups and semi‐structured interviews with doctors ( n = 31); registered nurses ( n = 19); and senior organisational managers ( n = 3) in a New Zealand tertiary hospital. Results: Safety was described as a core organisational value. Clinicians appreciated proactive safety approaches characterized by anticipation and vigilance, where they expertly recognized and adapted to safety risks. Managers trusted evidence‐based safety rules and approaches that recorded, categorized and measured safety. Conclusion and Implications for Nursing Management: It is important that nurse managers hold a more refined understanding about safety. Organisations are more likely to support safe patient care if cultural complexity is accounted for. Recognizing how different occupational groups perceive and respond to safety, rather than attempting to reinforce a uniform set of safety actions and responsibilities, is likely to bring together a shared understanding of safety, build trust and nurture safety culture.